Thrombin Time Dilution Test: A Simple Method for the Control of Heparin Therapy - Pizzuto, Javier; Garcìa-Méndez, Sergio; de-la-Paz Reyna, Marìa; Morales, Manuel R; Avilés, Agustìn; Zavala, Beatrìz; Gaos, Carlos (Thrombosis and Haemostasis, 1979)
A modification of the thrombin time test (TT), which permits quantitative measurement of plasma heparin activity during therapy is described. The prolonged TT of plasma containing heparin can be corrected by dilution with platelet-rich plasma (PRP). Clinical heparin activity is considered adequate when prolonged TT of the plasma can be corrected at dilutions of from 1:4 to 1:8 (±20%). In vitro studies of 30 PRP samples containing different amounts of heparin showed that 1:4 and 1:8 dilutions did not correct prolonged TT (P<0.05) in the presence of more than 0.2 and 0.3 U of heparin/ml respectively, indicating that the adequate dose of heparin should fall between those levels which show correction at these dilutions, using the diluted TT method.Patients treated with 100 U of heparin/kg every 4 or 6 h were studied: 52 without previous coagulation defects and 22 with disseminated intravascular coagulation (DIC). The results in the first group showed adequate dosage in 29 cases, overdosage in 12 and underdosage in 11. Hemorrhage occurred in 5 of the overdosage group. In the DIC series, 4 with underdosage of heparin did not improve; in 13 of 18 with adequate dosage, both hemorrhage and coagulapathy disappeared, while the other 5, with more severe complications did not improve. Based on these findings, the diluted TT appears to be a useful test in the assessment of heparin therapy, even in patients with previous coagulation abnormalities.